Báo cáo Tổng hợp ý kiến của các Đoàn đại biểu Quốc hội về dự thảo Luật Phòng, chống ma túy (sửa đổi) (Số: 4267/BC-TTKQH) - Tổng thư ký Quốc hội (2021)
Toàn văn Báo cáo Tổng hợp ý kiến của các Đoàn đại biểu Quốc hội về dự thảo Luật Phòng, chống ma túy (sửa đổi) (Số: 4267/BC-TTKQH)